A case study: the secondary students overall satisfaction on online learning - Mohd, Siti Munirah; Mohamad Jan, Nurhidaya; Mohd Idris, Fadzidah; Kaco, Hatika; Kamarudin, Shafinah (Universitas Atma Jaya Yogyakarta, 2024)
Online learning has revolutionized education by offering a flexible platform that transcends geographical boundaries and time constraints. It provides various multimedia resources, interactive exercises, and personalized feedback, enhancing the learning experience. However, online classes have challenges, such as decreased student engagement, technical issues, and a lack of structure, leading to procrastination and decreased productivity. This research aims to delve into the level of satisfaction experienced by talented high school students in terms of their virtual classroom experience. The study was conducted through an online survey using purposive and convenient sampling techniques. The data analysis showed that most students expressed satisfaction with the online classes, indicating that they found them informative, engaging, and meaningful. However, a few minor adjustments could be made to enhance students' experience, such as more opportunities for interactive participation, additional resources, and more precise instructions. Overall, the research highlights the positive impact of online education on the learning experience of gifted high school students.